Literature Review on the Role of Uterine Fibroids in Endometrial Function - Ikhena, Deborah E. (Reprod Sci, 2017)
Uterine fibroids are benign uterine smooth muscle tumors that are present in up to 8 out of 10 women by the age of 50. Many of these women experience symptoms such as heavy and irregular menstrual bleeding, early pregnancy loss, and infertility. Traditionally believed to be inert masses, fibroids are now known to influence endometrial function at the molecular level. We present a comprehensive review of published studies on the effect of uterine fibroids on endometrial function. Our goal was to explore the current knowledge about how uterine fibroids interact with the endometrium and how these interactions influence clinical symptoms. Our review shows that submucosal fibroids produce a blunted decidualization response with decreased release of cytokines critical for implantation such as leukocyte inhibitory factor and cell adhesion molecules. Furthermore, fibroids alter the expression of genes relevant for implantation, such as bone morphogenetic protein receptor type II, glycodelin, among others. With regard to heavy menstrual bleeding, fibroids significantly alter the production of vasoconstrictors in the endometrium, leading to increased menstrual blood loss. Fibroids also increase the production of angiogenic factors such as basic fibroblast growth factor and reduce the production of coagulation factors resulting in heavy menses. Understanding the crosstalk between uterine fibroids and the endometrium will provide key insights into implantation and menstrual biology and drive the development of new and innovative therapeutic options for the management of symptoms in women with uterine fibroids.